Social assessment of the E.P. group (Journal of Parents and Teachers, 2026)
Jesús Garrido Suárez describes how group dynamics can be analysed andevaluated in parent schools and educational settings. An example of a group selfassessment document combining three strategies is provided. The author highlights theimportance of the group feeling identified and being able to self-assess in order toimprove its functioning.
Keywords: Group, Assessment, Communication and Self-assessment